The Meaning of Bandopati Losari Mask dance as a Symbol of Cultural Expression - Bambang Yuniarto; Fia Fauziyah Sahidin (Formosa Journal of Multidisciplinary Research, 2023)
This journal aims to analyze the meaning of Topeng Kelana Bandopati Losari Dance as a symbol of cultural expression, This type of research is descriptive qualitative. The results of this study show that dance is a cultural heritage that is still very thick in its authenticity and shows the character of this nation. Mask dance character: Panji Sutrawinangun, Patih Jayabadra, Samba/Pamindo, Tumenggung Magangdiraja, Jinggano, Tumenggung-Patih, Kelana or Rahwana, Rumyang. The Kelana mask is a depiction of someone who is wrathful, greedy and unjust. Topeng Kelana dance is often associated with Panji stories. The character education values that we can apply daily from Topeng Kelana Bandopati are religious values, discipline, hard work, love for the country, responsibility, tolerance and helping.